2015
DOI: 10.1523/jneurosci.1890-15.2015
|View full text |Cite
|
Sign up to set email alerts
|

Re-Opening the Critical Window for Estrogen Therapy

Abstract: A decline in estradiol (E2)-mediated cognitive benefits denotes a critical window for the therapeutic effects of E2, but the mechanism for closing of the critical window is unknown. We hypothesized that upregulating the expression of estrogen receptor ␣ (ER␣) or estrogen receptor ␤ (ER␤) in the hippocampus of aged animals would restore the therapeutic potential of E2 treatments and rejuvenate E2-induced hippocampal plasticity. Female rats (15 months) were ovariectomized, and, 14 weeks later, adeno-associated v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 106 publications
2
45
0
Order By: Relevance
“…Exogenous estrogens have long been known to regulate many types of learning and memory mediated by the hippocampus and other brain regions (see (Bean et al, 2015; Daniel et al, 2015; Duarte-Guterman et al, 2015; Ervin et al, 2015; Foster, 2012; Frick, 2015; Frick et al, 2015; Korol and Pisani, 2015; Luine, 2014) for recent reviews). The current findings provide novel insight into the functional role of brain-derived estrogens on learning and memory in rodents.…”
Section: Discussionmentioning
confidence: 99%
“…Exogenous estrogens have long been known to regulate many types of learning and memory mediated by the hippocampus and other brain regions (see (Bean et al, 2015; Daniel et al, 2015; Duarte-Guterman et al, 2015; Ervin et al, 2015; Foster, 2012; Frick, 2015; Frick et al, 2015; Korol and Pisani, 2015; Luine, 2014) for recent reviews). The current findings provide novel insight into the functional role of brain-derived estrogens on learning and memory in rodents.…”
Section: Discussionmentioning
confidence: 99%
“…The ERs have similar distribution in female and male brains, but may differ in relative expression [77]. ER-α and ER-β expression patterns generally overlap, where ER-α is associated with reproductive behavior, whereas ER-β is associated with non-reproductive behaviors such as learning and memory [78] and anxiety-related behaviors. In hippocampus and cortical neurons, the estrogens-mainly E2 and other estrogenic ligands bind to membrane-associated and mitochondrial-associated G protein-coupled receptor (GPR 30), and activates the classical/ canonical nuclear and extranuclear orintra-cytoplasmatic ER isoforms-α and β-functioning as transcription factors [79][80][81], and a new type of nuclear ER, the orphan estrogenrelated receptor γ (ERR γ), which regulates dopaminergic neuronal phenotype [82], and IGF-1 receptor, which was recently recognized as a receptor for estrogens.…”
Section: Estrogen Receptors (Ers) Genetic Polymorphism and Epigenetimentioning
confidence: 99%
“…Conversely, ER-α changes are detected presynaptically in synaptic vesicles and postsynaptically in plasmalemmal and cytoplasmic regions of spine heads where protein translation occurs. In aged animals, it was demonstrated for the first time [78] that the window for E2-mediated benefits on cognition and hippocampal E2 responsiveness can be reinstated by increased expression of ER-α.…”
Section: Estrogen Receptors (Ers) Genetic Polymorphism and Epigenetimentioning
confidence: 99%
See 1 more Smart Citation
“…Other mechanisms are possible. Age and age-related chronic diseases change the expression of estrogen receptor-alpha and estrogen receptor-beta in the brain and how estrogen receptor-alpha responds to estrogen (30)(31)(32), which may contribute to differential effects of hormone therapy on cognition between the two cohorts. We have previously reported that the adverse impact of hormone therapy on cognitive function in the WHIMS cohort was strongest among women with lower baseline levels (2): Differences in the levels of education and the prevalence of risk factors for cognitive decline (hypertension, diabetes, cardiovascular disease) between the two cohorts may also contribute to differential hormone therapy effects.…”
Section: Long-term Effects Of Hormone Therapymentioning
confidence: 99%